Spying, war and mercantile competition in 17th Century The Jewish Portuguese Pedro de León Portocarrero, author of the Descripción del Virreinato del Perú - Carcelén Reluz, Carlos Guillermo (2009)
Although the Description takes the Viceroyalty of Peru as its subject, it is strongly focused on Lima, which occupies fully half of the text. Alongside a description of the urban plan of the city, its port, its defenses, and its communications with other regions, is a wealth of ethnographic detail about its inhabitants, plants, and the coastal environment in general. The next part reflects the author’s travels, along an itinerary from Lima to Cusco, Potosí, Buenos Aires, Tucumán, Chile, Arequipa, Ica and other coastal towns, before returning to Lima. Throughout, the author continues his ethnographic observation, though these are richest for Ica, where he had spent more time. The remainder of the account concerns the commercial connections of the viceroyalty, including Mexico and Central America. The final part is a description of ports in Panama and the Caribbean. The subject matter chosen indicates that the text was written for those with commercial interests, by someone who, like León Portocarrero, had direct experience in trade.